The Influence of Professionalism, Organizational Climate, and Work Motivation on The Performance of Private Madrasah Tsanawiyah Teachers in Batubara Regency - MZ, Ismail; Wijaya, Candra; Ananda, Rusydi (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research is based on issues related to teacher performance from the perspective of the variables of professionalism, organizational climate, and work motivation. The research method used is quantitative, employing an ex post facto approach. The research population consisted of 757 teachers from Madrasah Tsanawiyah in Batubara Regency, with a selected sample of 238 teachers spread across 53 madrasahs. The research results indicate: (1) professionalism (X1) has a direct influence on work motivation (X3) of Madrasah Tsanawiyah teachers in Batubara Regency by 45.00%; (2) organizational climate (X2) has a direct influence on work motivation (X3) of Madrasah Tsanawiyah teachers in Batubara Regency by 66.90%; (3) professionalism (X1) has a direct influence on teacher performance (X4) by 33.00%; (4) organizational climate (X2) has a direct influence on teacher performance (X4) of Madrasah Tsanawiyah teachers in Batubara Regency by 59.80%; (5) work motivation (X3) has a direct influence on teacher performance (X4) of Madrasah Tsanawiyah teachers in Batubara Regency by 37.50%; (6) professionalism (X1) has an indirect influence on teacher performance (X4) of Madrasah Tsanawiyah teachers in Batubara Regency through work motivation (X3) by 61.40%; and (7) organizational climate (X2) has an indirect influence on teacher performance (X4) of Madrasah Tsanawiyah teachers in Batubara Regency through work motivation (X3) by 65.60%.